Leaf and tiller dynamics in two competing C3 grass species: influence of neighbours and nitrogen on morphogenetic traits - Gatti, M. L. (2013)
The objective of this work was to analyse the competitive interactions between Bromus willdenowii Kunth. (BW = prairie grass) and a perennial C3 grass Dactylis glomerata L. (DG = cocksfoot) through morphogenetic traits, during pasture establishment. Four combinations of species (pure BW, pure DG, DG flanked by BW and BW flanked by DG plants), with and without winter nitrogen fertilization, were factorially arranged in a complete random block design. Data were recorded on three tiller age cohorts of the central target plant: the main stem and those that appeared 20 and 30 days after fertilization (daf). Leaf elongation rate (LER) of the older tillers was the only variable affected by nitrogen addition. Annual neighbours, which showed higher LER than perennial ones, caused a decrease in leaf lifespan in the younger tillers and a delay in the leaf appearance rate on the main stem and on 20-daf tillers, and the tiller appearance rate. Annual neighbours controlled leaf and tiller dynamics and therefore restricted the vertical and horizontal space occupation of the target plant. These results reinforce the advantage of using a low seeding rate for the annual species to avoid negative effects on perennial grass establishment and persistence.